Control de constitucionalidad y Muerte Cruzada en Ecuador - Tipantasi Carreño, John Erick (2024)
In the context of the Ecuadorian legal system, the figure of the “Muerte Cruzada” (crossed death) and the control of constitutionality are presented as issues of great relevance and debate. This research focuses on the power granted to the President of the Republic to dissolve the Legislative Branch through an Executive Decree, known as "Muerte Cruzada", and explores to what extent this power affects the principles of constitutionality control and the health of the democratic system. The research approaches the interaction between the executive and legislative branches in moments of crisis, examining how this dynamic can impact the balance of power and democracy in Ecuador. The lack of constitutional control over two of the three grounds that allow the dissolution of the National Assembly through the "Muerte Cruzada" is questioned, which could have implications for accountability and government transparency. The analysis is justified by the need to fully understand the constitutional mechanisms that regulate power relations in situations of political crisis. The objectives of the investigation are to analyze the causes that support the "Muerte Cruzada" in Ecuador and to examine the orders issued by the Constitutional Court in recent cases on the alleged unconstitutionality to dissolve the legislative power and to evaluate the control of constitutionality in the use of this figure. The research is carried out considering multiple perspectives, such as legal, historical and political, and explores the interpretation and application of the relevant regulations. Through this analysis, we seek to understand how the relationship between state powers manifests itself at crucial moments and how constitutional control can influence the democratic principles and the rule of law in Ecuador.